– The dualism of death and life in the elegy of Ibn Alromi to his mother – Stylistics study - Al Mashaykh, Mohammed Mahmoud; Al Hourani, Mohammed Issa (Journal of Humanities & Social Sciences, 2019)
There is no doubt that Ibn al- Rumi learned from the flags of Arabic poetry, and pole of the Abbasid poetry poles.. Known strangely of its stages and its development and pessimism after the rotation of the ages of time, Vjj not once inherited by bitterness and pessimism, and tattooed in his body and the idea of ​​wounds do not heal, His poetry deep into the depth of his experiences, shaking with burning hot emotions, burning from the burning of several, most notably the burning of death; he suffered in his life to lose all those who loved, and the death of his sons one after the other, even Fjjdh fate by his mother, and this tragedy was more than what it was based on the past tense; This is a long tradition that we have proactively borrowed Death and life on which it was based.We have seen the division of the poem into several parts connected to each other by a sensory flow that grows from one section to another, with antennas that regulate existence in the two spheres of life and death.
Keywords: Ibn al-Roumi; lamentation of the mother; a stylistic study